Resveratrol prevents TNF-α-induced VCAM-1 and ICAM-1 upregulation in endothelial progenitor cells via reduction of NF-κB activation. Issue 9 (September 2020) - Zhang, Yefei; Liu, Huahua; Tang, Weiliang; Qiu, Qiongya; Peng, Jiahao
Objective: To assess the effects of resveratrol (RSV) on expression of adhesion molecules in endothelial progenitor cells (EPCs) following tumor necrosis factor-α (TNF-α) stimulation. Methods: EPCs were treated with RSV and stimulated with TNF-α. A mononuclear cell (MNC) adhesion assay was used to assess the effects of RSV on TNF-α-induced MNC adhesion. Vascular cell adhesion molecule-1 (VCAM-1), intercellular adhesion molecule-1 (ICAM-1) and E-selectin expression levels and nuclear factor κB (NF-κB) activation were assessed by immunoblotting. Results: MNC adhesion to TNF-α-treated EPCs and VCAM-1/ICAM-1/E-selectin levels in EPCs were increased following TNF-α stimulation and decreased following RSV treatment. TNF-α enhanced NF-κB inhibitor α (IκB-α) phosphorylation in the cytosol as well as nuclear NF-κB p65 levels, both of which were decreased by RSV. Conclusions: These findings provide new insights into RSV's anti-inflammatory and anti-atherosclerotic effects. RSV's mechanism of action might involve downregulation of VCAM-1, ICAM-1 and E-selectin by partial blockade of TNF-α-induced NF-κB activation and IκB-α phosphorylation in EPCs.